The Effects of School Operational Assistance and School Facilities and Infrastructure on Educational Quality in Public Elementary Schools in Tungkal Ilir District, Banyuasin Regency - Pujiati; Meilia Rosani; Djunaidi (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study analyzed the effects of School Operational Assistance (BOS) and school facilities and infrastructure on educational quality in public elementary schools in Tungkal Ilir District, Banyuasin Regency. A quantitative ex post facto design was employed. The population consisted of 193 teachers, and 130 respondents were selected using the Slovin formula at a 5% margin of error. Data were collected through Likert-scale questionnaires and documentation. The instruments were valid and highly reliable, with Cronbach's alpha coefficients of 0.920 for BOS, 0.906 for facilities and infrastructure, and 0.907 for educational quality. Data were analyzed using descriptive statistics, prerequisite tests, simple linear regression, and multiple linear regression with SPSS version 26. BOS had a positive and significant effect on educational quality (B = 0.386; t = 7.491; p < 0.001; R² = 13.6%). Facilities and infrastructure also had a positive and significant effect (B = 0.566; t = 8.183; p < 0.001; R² = 34.3%). Simultaneously, both variables significantly predicted educational quality (F = 42.105; p < 0.001; R² = 39.9%), with the regression equation Y = 0.723 + 0.253X₁ + 0.510X₂.. The findings indicate that educational quality requires accountable and instruction-oriented BOS management together with adequate, accessible, and well-maintained school facilities.